810-nm Photobiomodulation Evokes Glutamate Release in Normal and Rotenone-Dysfunctional Cortical Nerve Terminals by Modulating Mitochondrial Energy Metabolism - Silvia Ravera; Elisa Farsetti; Guido Maura; Manuela Marcoli; Matteo Bozzo; Chiara Cervetto; Andrea Amaroli (Cells)
The dysfunction of mitochondria, the primary source of cellular energy and producer of reactive oxygen species (ROS), is associated with brain aging and neurodegenerative diseases. Scientific evidence indicates that light in the visible and near-infrared spectrum can modulate mitochondrial activity, a phenomenon known in medicine as photobiomodulation therapy (PBM-t). The beneficial effects of PBM-t on dementia and neurodegeneration have been reviewed in the literature. However, the molecular mechanisms underlying these findings have yet to be fully elucidated. This study investigates the mechanism behind dose-dependent glutamate release in nerve terminals after irradiation with 810 nm, 1 W for 60 s continuous, 1 cm2, 1 W/cm2, 60 J, 60 J/cm2 (810 nm-1 W) or 810 nm, 0.1 W for 60 s continuous, 1 cm2, 0.1 W/cm2, 6 J, 6 J/cm2 (810 nm-0.1 W), focusing on mitochondrial activities. The results show that PBM modulated the mitochondrial metabolism of cortical nerve terminals and supported a power-dependent increase in oxidative phosphorylation (OxPhos) activity when stimulated with pyruvate plus malate (P/M) or succinate (succ) as respiratory substrates. The PBM-induced increase in OxPhos was sensitive to adding rotenone (Complex I inhibitor) and antimycin A (Complex III inhibitor) when synaptosomes were stimulated with P/M, but only to antimycin A when stimulated with succ. This allowed us to observe that the glutamate efflux, disrupted in the presence of rotenone, was partially restored by PBM due to the increase in the OxPhos pathway led by Complex II. This evidence suggests that PBM, acting on mitochondria, could facilitate physiological communication within the neuron-astrocyte network through vesicular glutamate release, potentially regulating healthy brain function and brain dysfunction.